Increasing the Potential of Sports Teachers in Exploring the Potential of Outstanding Athletes Through Early Identification of Sports Talent - Maulidin, Maulidin; Amalia Rachman, Irna Ningsi; Kurniawan, Edi; Syarifoedin, Elya Wibawa; Muhsan, Muhsan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Talent identification is important to find potential talented athletes at an early age to be trained to a high level of achievement. This talent identification is intended to estimate the probability of children who are talented in sports to be able to succeed in undergoing a training program so that they are able to achieve their peak achievements. Every child is unique, as is the potential or talent they have. The uniqueness of each child must be fully realized by a teacher/coach in developing children into future athletes. As we know, every child has a certain potential/talent in sports. This potential must be explored with a science and technology approach to be developed to a further level. The identity of Physical Education develops along with the evolution of society and its supporting sciences, including sports science. This evolution provides the identity of physical education as an academic discipline and physical education as a life profession. Almost every school has extracurricular sports. Extracurricular activities are a place for students to channel their interests and talents outside of academic lessons at school so that not a few high-achieving athletes are born from extracurricular activities in schools. For that, the trainer must understand the characteristics of the child and recognize the growth and development of the child's movement which is then used as a reference to recognize the potential of early childhood to be trained. The process of achieving achievement is effective if the athletes being trained are selected athletes who have the potential that matches the demands of the specifications of the sport. The athlete's achievement is not only in their training, but must also build the mentality of the athletes in applying Sports Science.